Association Between Anti-Tuberculosis Drug (OAT) Adherence and Tuberculosis Recurrence Among Pulmonary TB Patients at Dr. Pirngadi Regional Hospital, Medan - Metia Ariani Br Ginting; Heppy Jelita Sari Batubara; Hapsah Hapsah; Mila Trisna Sari (Jurnal Kesehatan dan Kedokteran, 2026)
Pulmonary tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a major public health problem. Treatment success depends heavily on adherence to anti-tuberculosis drug (ATD) therapy; however, the long treatment duration may reduce adherence and increase the risk of recurrence. Objective: This study aimed to describe the demographic characteristics of pulmonary TB patients and to analyze the association between adherence to ATD therapy and TB recurrence at Dr. Pirngadi General Hospital, Medan. Methods: A quantitative observational analytic study with a cross-sectional design was conducted among 33 pulmonary TB patients treated at Dr. Pirngadi General Hospital, Medan (November–December 2025). Data were collected using an ATD adherence questionnaire and complemented with medical record data. Descriptive statistics were used to summarize patient characteristics, adherence levels, and recurrence status, while the Chi-square test was applied to assess the association between adherence and recurrence (p < 0.05). Results: Most respondents exhibited low adherence to ATD therapy (66.7%), and a high proportion experienced TB recurrence (78.8%). The majority were male (51.5%), predominantly in the adult age group (41–60 years; 51.5%), had a senior high school education (87.9%), and were self-employed. A statistically significant association was found between adherence to ATD therapy and TB recurrence (p = 0.046). Implications: These findings reinforce the need to strengthen adherence-support strategies in hospital TB services, including structured counseling, active follow-up, and family or treatment supervisor involvement, to reduce recurrence risk and improve program outcomes. Originality/Value: This study provides facility-based evidence from Dr. Pirngadi General Hospital, Medan, demonstrating a significant relationship between adherence level and recurrence status, offering locally relevant data to guide targeted adherence interventions and recurrence prevention in hospital settings.